Entre a macropolítica e a micropolítica : a formação continuada do professor do curso de Administração - Faria, Ana Paula Ribeiro (2012)
The study seeks to understand the formative movements that take place inside a group of professors from a Business Administration undergraduate course in a private Institution. At this meaning, considering that a great part of the knowledge in Business Administration still represents itself in a functionalist dimension, other lines cross its constitution possibly coming to modify the ways of current experimented functioning. In face of this, the raising question is how the continued education development of the professors at the mentioned course has happened and what implications, on the acting ways, the professors experiment? Objective, however, to understand how the affection produced on the process of the continued education potentially enable the professor pratics, as well as understand the meanings of being a teacher at the interplaces constituted at the private superior Institution of teaching. It were used pieces of Deleuze, Gualttari and Espinosa as main intercessors. It takes as group/person of research the professors that integrate a daily university routine of a private Institution, located at the city of Vila Velha/ES. The production of data happened by keeping up with some selected professors in the very investigative process, according to the affections produced at the research meeting. For this purpose, we used the resource of conversations with the trainees, where the production by means of the cartographyc methodology, it is not talking about the other, nor in the place of the other, thus, a double capture that is above all, something that is between and out of the subject and the researcher, that takes another direction, composing another view. In this context, the intention of the investigation it is not to search the comprehension of the higher education professors’ duties, but to expand our perception, in what concerns the powers that makes us wish for the teaching profession and enlace ourselves at the education processes in a way that we are capable to place our own problems. Thus, being open to the vibratibility in the course of the production is to be open for the sensible to make itself present, where the happening makes itself through the unexpected. Therefore, it is in the process of experience that we can find out other means where the sensible sensitive leak that empower the professors to compose as other landscapes that affect and constitute them